Gender Comparison of Medical Student Microsurgical Skills in a Laboratory Model - Sudario-Lumague, Rowena; Chiang, Yuan-Cheng; Lin, Tsan-Shiun (Journal of Reconstructive Microsurgery, 2018)
Background Perceived gender-related differences in surgical skills could limit opportunities available for any aspiring surgeon. There should be more available literature and logical analysis of these observations. The objective of this study is to evaluate the microsurgical skills of male and female medical students using a standard scale in the laboratory.Methods This study included medical students enrolled in the Kaohsiung Chang Gung Memorial Hospital from 2002 to 2015 who were evaluated by a senior consultant for their microsurgical skills. A standard numeric scale was used to evaluate their suturing technique after basic microsurgical training. Differences in the scores between male and female medical students were evaluated using statistical analysis.Results A total of 578 medical students were included in the study. There were 393 males (68%) and 185 females (32%). Using statistical analysis, there is no significant difference in the distribution of scores (p-Value = 0.78) and mean scores (p-Value = 0.75) between the two groups.Conclusions This study shows that microsurgical skills of male and female medical students are similar. Equal opportunities in the eventual pursuit of the surgical specialties should be available regardless of gender.
Keywords: microsurgical training; gender comparison; microsurgical skill; microsurgery; basic surgical skill; gender difference